2022
DOI: 10.1515/med-2021-0397
|View full text |Cite
|
Sign up to set email alerts
|

Association between preventable risk factors and metabolic syndrome

Abstract: The risk factors associated with metabolic syndrome (Met-S) including hypertension, hyperglycemia, central obesity, and dyslipidemia are preventable, particularly at their early stage. There are limited data available on the association between Met-S and preventable risk factors in young adults. We randomly selected 2,010 Saudis aged 18–30 years, who applied to be recruited in military colleges. All the procedures followed the guidelines of International Diabetes Federation. The results showed that out of 2,01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Physical activity and cardiovascular fitness in Saudi females is an essential area of study due to the high prevalence of CVD in Saudi Arabia. It was reported that, earlier, Saudi females lacked access to sports and physical education, resulting in high rates of obesity and compromised health [ 15 ]. Hence, the study was conducted to assess BC's influence on adult females' CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and cardiovascular fitness in Saudi females is an essential area of study due to the high prevalence of CVD in Saudi Arabia. It was reported that, earlier, Saudi females lacked access to sports and physical education, resulting in high rates of obesity and compromised health [ 15 ]. Hence, the study was conducted to assess BC's influence on adult females' CRF.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Met-S is becoming highly prevalent even in young adults [ 2 ]. Many of the risk factors associated with Met-S including hypertension, hyperglycaemia, central obesity, and dyslipidemia are preventable and can be controlled by modifications in dietary habits and physical activity, particularly at their early stage [ 3 ]. Moreover, uncontrolled hyperglycaemia has also been directly associated with dyslipidemia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the importance of avoiding smoking, controlling alcohol consumption, and exercising, all of which can help an individual maintain a healthy lifestyle [ 12 , 27 , 28 ]. An unhealthy lifestyle is significantly associated with the prevalence of metabolic syndrome [ 29 ]. Metabolic syndrome is a factor that greatly affects health, one’s tendency to use healthcare services, and healthcare costs [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome has been reportedly associated with the incidence and mortality of various cancers, such as breast and rectal cancer; therefore, diagnosing and treating metabolic syndrome is of great clinical importance, and the condition should be managed to reduce disease burden [ 32 , 33 ]. It is also a meaningful predictor of one’s tendency to use healthcare services because metabolic syndrome is a preventable risk factor and not something which should require emergency treatment [ 29 ]. Since healthy lifestyle and metabolic syndrome factors are also associated with low socio-economic status [ 29 ], paying attention to what makes a healthy lifestyle and the factors related to metabolic syndrome, specifically regarding medical aid recipients, are necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation